Supramolecular self-assembly of a new multi-conformational Schiff base through hydrogen bonds: Crystal structure, spectroscopic and theoretical investigation - Rocha, Mariana (2017)
The compound 4-(4-dimethylaminobenzylidene)aminoacetophenone was synthesized by condensation of 4-aminoacetophenone and 4-(dimethylamino) benzaldehyde in ethanol. This compound was characterized by CG-MS, infrared, Raman, UVeVis, 1H and 13C NMR spectroscopy. The crystal structure was solved by single-crystal X-ray diffraction methods. The crystallographic data reveals that there are four independent molecules per asymmetric unit, that mainly differ from one another in rotations around the σ-bond of the azomethine N-atom with the phenyl ring. A detailed analysis of the intermolecular interactions in the four conformers of the compound has been performed using Hirshfeld surfaces and their associated two-dimensional fingerprint plots. The optimized geometrical parameters and calculated spectroscopic features obtained by quantum chemical calculations at B3LYP method show a very good agreement with the experimental data. Moreover, Natural Bond Orbital (NBO) analysis confirms the strong hyper-conjugative LP N(n1) → σ* C(n9)–H interaction between the lone pair located in the N-atom of the azomethine group and the C–H bond. Liquid crystalline properties of the Schiff base were studied by differential scanning calorimetry (DSC), polarizing optical microscopy (POM) and Powder X-ray diffraction techniques. Mesomorphic behaviour was observed in this unsymmetrical azomethine. Based on POM and DSC measurements, the hexatic Smetic B phase was detected.